2020
DOI: 10.3390/ijerph17218169
|View full text |Cite
|
Sign up to set email alerts
|

Current Pharmacological Treatment of Type 2 Diabetes Mellitus in Undocumented Migrants: Is It Appropriate for the Phenotype of the Disease?

Abstract: Type 2 diabetes is increasingly recognized as a spectrum of metabolic disorders sharing chronic hyperglycaemia. In Europe, the continually growing number of migrants from developing countries could affect diabetes phenotypes. We evaluated a population of 426 Italians and 412 undocumented migrants. Using 17 variables (with the exclusion of ethnic origin) we performed a multiple component analysis to detect potential clusters, independently from ethnicity. We also compared the two groups to evaluate potential et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
1
6
1
Order By: Relevance
“…The relative risk of diabetes was significantly higher in Asians and Latin Americans. This is in keeping with the observation that the frequency of type 2 diabetes is higher in migrants of all ethnicities and that they develop this disease at an earlier age than native Europeans 35 , though ethnic origin does not appear to be the only explanation 30 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The relative risk of diabetes was significantly higher in Asians and Latin Americans. This is in keeping with the observation that the frequency of type 2 diabetes is higher in migrants of all ethnicities and that they develop this disease at an earlier age than native Europeans 35 , though ethnic origin does not appear to be the only explanation 30 .…”
Section: Discussionsupporting
confidence: 86%
“…Nevertheless, we have already shown that the treatment of chronic conditions—either alone or associated with other diseases—is limited to pharmacological interventions not very different from those implemented for patients belonging to the general population 29 , 30 . This could be due to the fact that NGOs have very scarce possibilities to impact on social and economic determinants; therefore, other types of intervention are almost impossible.…”
Section: Discussionmentioning
confidence: 99%
“…The considerations made above are far from explaining the differences in antidiabetic therapy between our groups of Italians and undocumented migrants with diabetes. Though the latter might have a different prevalence of diabetic phenotypes [13], we have already demonstrated that pharmacologic treatment of diabetes does not appear to be based on disease phenotypes [23] and the present observations also do not point in the direction of phenotype-based therapeutic decisions. To an even lesser extent do they seem to be explained by efforts to take into account the potential pharmacogenetics aspects of diabetes [24].…”
Section: Discussioncontrasting
confidence: 56%
“…In spite of this, we have already shown that the treatment of chronic conditions, either alone or associated to other diseases is limited to pharmacological interventions not very different from those implemented for patients belonging to the general population [26,27]. This could be due to the fact that NGOs have very scarce possibilities to impact on social and economic determinants; therefore, other types of intervention are almost impossible.…”
Section: Discussionmentioning
confidence: 99%